Nucleon magnetic moments in light-front models with quark mass asymmetries - Araújo, W. R. B. de; Trevisan, L. A.; Frederico, T.; Tomio, L. [UNESP]; Dorokhov, A. E. (Sociedade Brasileira de Física, 2004)
We show that the systematic inconsistence found in the simultaneous fit of the neutron and proton magnetics moments in light-front models, disappears when one allows an asymmetry in the constituent quark masses. The difference between the constituent quarks masses is an effective way to include in the nucleon model the effect of the attractive short ranged interaction in the singlet spin channel.